Plasma-Assisted Simultaneous Reduction and Nitrogen Doping of Graphene Oxide Nanosheets - MCEVOY, NIALL (My University, 2013)
An environmentally benign and scalable route for the production of gram scale quantities of nitrogen-doped graphene using a downstream microwave plasma source is reported. Simultaneous reduction and doping of graphene oxide is achieved and the process negates the need for high temperatures and toxic solvents associated with existing methods. This gas-phase low temperature process is completely dry and, thus, minimises re-aggregation of graphene flakes which is typically associated with liquid phase reduction methods. The resulting material has many potential uses, particularly in electrochemical energy.
PUBLISHED
Keywords: Graphene; Nanoscience & Materials